An Analysis of Ibnu Khaldun's Thoughts About Islamic Rationalism - Ahmad Nabil Amir (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2022)
This paper briefly discusses Ibn Khaldun’s philosophical and rational construction of Islam and its metaphysical discursus as set forth in his classical works such as Kitab al-‘Ibar, Al-Ta‘rif, Tahrir al-Ahkam, and al-Muqaddimah. This work expressed his highly rational outlook that developed a critical and rational understanding of religious and moral premises. It also summarized its dynamic ground that contributes to expound instructive discussion of related ideas and themes. The study is based on library research using content analysis and analyzed through analytical and descriptive approaches. The finding concludes that Ibn Khaldun has brought forth a rational interpretation of history based on the unique philosophical and socio-cultural analysis he introduced in his al-Muqaddimah. This characteristic approach of the rational ideal has significantly impacted Islam’s modern history and tradition. His rational and argumentative principle has largely influenced the works of contemporary Muslim thinkers such as Malik Bennabi, Rashid Ghannoushi, and Muhammad Asad.